INTERNET COMMUNICATION: NEW CHALLENGES FOR THE YOUTH - D. N. Karpova (MGIMO University Press, 2013)
Many social scientists are deeply concerned with the problem of youth cyber dependency. It is primarily caused by people’s “submergence” into the newest technological gadgets and virtual reality. In sociological lexis one can even meet such a term like “youth go online”. The author proposes a definition for that term applied to describe people who use electronic smartphones most part of their day (in some cases even like a background all day long). However we can’t diminish all advantages associated with the Internet using. It is both quick access to any information and distance education, the possibility to transfer money in a second through the whole world and other. But here the author stresses upon another side of Internet using. The paper reveals some forms of social and psychological challenges and deviance behavior while active using of virtual mass communication tools. Moreover, the article observes the most fundamental research in the sphere of sociology of youth and mass communication conducted by famous Russian and International scientists. Their studies reveal that young internet users sometimes lose a strong connection with the real world which is caused by informational overloading or “computer hunger”. On the base of the empirical data made by the Sociological School of The Moscow State University of International Relations (MGIMO-University), there was made an attempt to clarify the youth understanding of such phenomenon like internet-responsibility for the content users post and what do students mean by the term “cybersecurity”? Besides above-mentioned personal security, special attention is paid to the problem of international cyber terrorism which can cause more damage not only to companies but the whole governments. In that connection the article discloses the functioning of international organizations like United Nations, European Union and Council of Europe aimed to the prevention of destructive forms of internet using and creation of global culture of cybersecurity.